Increase in rabies cases during COVID-19 pandemic: Is there a connection? - Reyhaneh Rasizadeh; Hossein Bannazadeh Baghi (Journal of Infection in Developing Countries)
Increase in rabies cases during COVID-19 pandemic: Is there a connection?